Reduction in exposure of interventional cardiologists to ionising radiation over a 10-year period. (15th May 2018) - Faroux, Laurent; Blanpain, Thierry; Nazeyrollas, Pierre; Tassan-Mangina, Sophie; Heroguelle, Virginie; Tourneux, Christophe; Baudin, Florian; Metz, Damien
Abstract: Exposure of operators to ionising radiation in interventional cardiology has likely diminished, but data confirming the magnitude of the reduction are lacking. The aim of this study was to compare the dose of radiation received by interventional cardiology operators at 11 years interval (2006 vs 2017). The study population comprised all interventional coronary procedures performed by a single operator in one catheterization laboratory (cathlab) of a large university hospital in north-eastern France. Exposure was compared between two periods, namely period 1 (from October 2005 to March 2006) and period 2 (from March 2017 to June 2017). The primary endpoint was the dose of radiation received by the operator, measured using an electronic dosimeter placed on the operator's left arm. In 2017, the dose of radiation received by the operators was, on average, 95% lower than the dose received in 2006 ( p < 0.0001), even though the average fluoroscopy time increased by 73% over the same period (p < 0.0001). By multivariable analysis including body mass index, fluoroscopy time and performance of at least one (1) coronary angioplasty, the reduction in the operator's exposure to radiation remained significant. The dose of radiation received by interventional cardiology operators has decreased by 95% over the last ten years. Highlights: The spectacular decrease in the dose of radiation received by interventional cardiologists and patients undergoing coronary procedures could encourage operators to undertake longer and more complex procedures.